Exploration of main international markets for tropical flowers from Tequendama province (2011)
The tropical flowers crops in the Tequendama province (Cundinamarca) have risen as an economic, social, and environmental alternative due to competitive and comparative advantages of the province. In this paper appear the results of the evaluation of tropical flower production in the Tequendama province during the first semester of 2006. The productive potential of this province was compared with national production and exploration of the international market for cut flowers, including that of tropical flowers, presenting the current situation of the market, the latest tendencies and establishing the opportunities of some markets for the export of tropical flowers from Colombia. The type of study was an exploratory-descriptive one. For evaluation of production in the province of Tequendama, personal interviews were made in the field with producers of tropical flowers. The exploration of international markets was made using information from secondary sources and international data bases. The research concluded that the market of tropical flowers was each time more demanding in quality, diversity and frequency of shipments. The appearance of new competitors with high market power demands that the producers from the Tequendama province improve the quality and volume of production with the purpose of maintaining a constant supply to the market and orienting the production towards the still unsatisfied international markets, especially those of the United States and the European Union.